Nano-encapsulation: overcoming conductivity limitations by growing MOF nanoparticles in meso-porous carbon enables high electrocatalytic performance - Sathiyan, Krishnamoorthy (2023)
Among the methods employed for carbon capture, the electroreduction of CO2 offers both a reduction in CO2 levels and the possibility of recycling it into commodity chemicals. However, the most efficient catalysts for this reaction are precious metals. To achieve cost-effective processes, other elements should be used. Transition-metal atoms coordinated with metal-organic frameworks (MOFs) exhibit high performance as electrocatalysts. However, the isolating natures of MOFs limit their utilization as electrocatalysts. In this study, we grew MOF nanoparticles inside hierarchically mesoporous carbon instead of mixing the MOFs with conductive carbon. The incorporated MOF nanoparticles showed improved properties compared with those of MOFs mixed with carbon, indicating strong electronic interactions in the composites. The encapsulated MOF nanoparticles demonstrated high electric conductivity while preserving their original crystallinity. When used as electrodes in CO2 electroreduction, the MOFs exhibited a high electroactive coverage of 155 nmol cm−2. Moreover, in a CO2-saturated electrolyte, the composites exhibited excellent electrochemical performance, including a small onset potential (−0.31 V vs. RHE) and large reduction currents (−18 mA. cm−2 at −1.0 V); these were considerably higher than those usually reported for MOF-based materials except in CO electroreduction. Importantly, the composite produced valuable hydrogenated commodity chemicals, including formic acid.